Career planning for physical disability students - Nusantara, Syafrudin Bayu; Barida, Muya; Hestiningrum, Erni; Nugraha, Ariadi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2020)
Career Planning for Students with Physical Disabilities is crucial to be prepared. A good career planning picture must contain four aspects of career planning which consist of seeking information, understanding, making decisions, and career achievement. The purpose of this study was to explore in-depth career planning in students of the Special School for Physical Disabilities (SLB) 1 Yogyakarta. This study used a qualitative approach, with the type of case study research, the subjects in this study were two students with physical disabilities, the first subject had moderate cerebral palsy and the second subject experienced abnormalities in the muscle system and skin groups. (musculus skeletal system) spina bifida. Then the secondary sources are teachers and parents. The data collection technique used triangulation in the form of interviews, observation, and documentation. The results of the study concluded that the career planning of the two early TA and DI students had differences. TA has not been able to do career planning. Because in the search for information, understanding, decision making, and career skills, TA cannot do it. Meanwhile, DI is capable of career planning because DI can find career information, even though DI is still a little doubtful due to lack of confidence, DI career decision making can be even though it is still not effective in managing free time. DI career skills are said to be capable, even though DI does not attend any additional education (courses).